2017
DOI: 10.7860/jcdr/2017/22650.9395
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Deferasirox as an Oral Iron Chelator in Paediatric Thalassaemia Patients

Abstract: Introduction: Thalassaemia Major patients require frequent blood transfusion leading to iron overload. Excessive iron gets deposited in vital organs and leads to dysfunction of the heart, liver, anterior pituitary, pancreas, and joints. Our body has limited mechanism to excrete iron, so patients with iron overload and its complications need safe and effective iron chelation therapy. Aim:To assess the efficacy of Deferasirox (DFX) as an iron chelator, with specific reference to reduction in serum ferritin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…5. Chelation Therapy in studied patients: Deferasirox alone in a dose of 20-30 mg/kg/day once daily before meals [17], or Desferrioxamine alone 20-40 mg/kg/day for 6 days /week but in patients with persistently high serum ferritin levels above 3000 ng/ml, Deferasirox is combined with Desferrioxamine in a dose of 20-40 mg/kg/day for 10 days per month either by subcutaneous infusion using infusion pump in 8-12 hours/day or by continuous intravenous infusion for 8-10 hours/day (combined chelation therapy [18].…”
Section: Radiologicalmentioning
confidence: 99%
“…5. Chelation Therapy in studied patients: Deferasirox alone in a dose of 20-30 mg/kg/day once daily before meals [17], or Desferrioxamine alone 20-40 mg/kg/day for 6 days /week but in patients with persistently high serum ferritin levels above 3000 ng/ml, Deferasirox is combined with Desferrioxamine in a dose of 20-40 mg/kg/day for 10 days per month either by subcutaneous infusion using infusion pump in 8-12 hours/day or by continuous intravenous infusion for 8-10 hours/day (combined chelation therapy [18].…”
Section: Radiologicalmentioning
confidence: 99%
“…[ 7 ] The iron overload resulting from the timely blood transfusions is the culprit of the disease process in thalassemia patients that can lead to organ injury and collapse. [ 8 ] In thalassemia patients, treatment with iron-chelating agents have demonstrated significant decline in organ damage due to iron overload and enhance survival rate. [ 9 ] Of late, there are three iron-chelating agents available on the market for the management of iron burdens such as deferoxamine, deferasirox, and deferiprone.…”
Section: Significance Of Iron Chelation Therapymentioning
confidence: 99%
“…[ 6 12 ] These patients require safe and effective iron chelation therapy as our body has a restricted physiologic mechanism to eliminate iron. [ 8 ] Primarily, the iron chelators bind to labile iron molecules with low molecular weight, so at any time only a minor portion of human body iron is accessible for chelation. [ 2 ] Therefore, the treatment with an iron-chelating agent is maximum effective if its activity exists throughout the day.…”
Section: Significance Of Iron Chelation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“… 43 JaiSwal et al later reported a significant mean reduction in SF of 1207.11 ng/ml (32.38% decrease) after 12 months therapy with DFX at a mean dose of 38 mg/kg/d in 45 heavily transfused thalassemia patients. 44 A prospective observational study including 176 patients with TDT (total 267), reported long-term results in pediatric patients treated with DFX and documented a decrease in median SF of 575 ng/ml after five years of DFX therapy with a mean dose of 25.8 mg/kg/d. 45 A Cochrane review reported by Bollig et al indicated similar efficacy of DFX as compared to DFO (depending on the ratio of DFX to DFO dose, generally showing similar results at a mean ratio of 1 mg of DFX to 1.8 mg of DFO).…”
Section: Evidence In Tdtmentioning
confidence: 99%